Model Pembelajaran Sosiosaintifik Blended Project-Based Learning (PJBL) Dalam Pembelajaran IPA di SMP/MTS Se-Boyolali - D Djumadi; Rina Astuti; Lina Agustina; Annur Indra Kusumadani (Jurnal TUNAS, 2021)
Learning with Socioscientific Blended Project-Based Learning is a learning process that actively involves students both online and outside the network in reading, writing, conducting experiments, and analyzing, as well as finding solutions to social science-related problems in society. The use of the Blended Project-Based Learning (BPjBL) model is considered very beneficial because it can improve problem-solving and critical thinking skills. This community service aims to introduce the right Blended Project-Based Learning (BPjBL) learning model to improve students' thinking skills, namely the ability to think clearly and rationally which includes the ability to think reflectively and independently with a Socioscientific issues (SSI) approach that is able to produce learning products. HOTS (Higher Order Thinking Skill) orientation. This training is expected to provide skills to develop learning models for SMP/MTS teachers and apply them in science (Biology) learning. This training was attended by MGMP IPA (Biology) teachers throughout Boyolali, amounting to approximately fifty people, where the implementation is planned to last for 4 days, namely 21-24 August 2021